(untitled) (Journal of Educational Sciences, 2025)
The comprehensive and fundamental changes in the educational system will not fail to affect rural schools, especially small-integrated schools. Rural small-integrated schools are the main component of the national education system, as well as the main means of training personnel for the development agricultural production and rural culture. The organization of the educational process in small-integrated schools places special requirements on the teacher’s training and approach to his professional activity. The article analyzes the prospects and problems of developing of small-integrated schools in Kazakhstan today and recommendations for teaching geography in small-complex schools. At the same time, the role of such schools in preserving settlements, expanding traditional branches of the economy, improving the demographic situation, and creating a space for cultural education in rural society is considered. The research findings are aimed at providing methodological assistance to teachers and improving the quality of education in small schools. The methodological techniques (subject integration, "vertical work") and tasks in teaching geography for small-integrated schools are summarized. An expert survey of 25 teachers of small-integrated school in the Turkestan region was conducted. Teaching geography in small-integrated schools presents unique challenges and opportunities, shaped by the school’s size, resource availability, and student composition. These schools, often located in rural or sparsely populated areas, typically combine multiple grade levels into a single classroom, requiring innovative teaching approaches to accommodate diverse age groups and learning needs. Key words: education, small-integrated school, combined class.